Belgium and the European arrest warrant : is European criminal cooperation under pressure? Refusal of European arrest warrant surrender in the case Jauregui Espina as proof of failing mutual trust - Meysman, Michaël (2016)
In its judgment of the 19th of November 2013, Belgium’s highest court, the Court of Cassation, confirmed an earlier judgment of the so-called kamer van inbeschuldigingstelling (KI) of the Court of Appeal in Ghent in response to a surrender demanded in accordance with a number of European arrest warrants issued by Spain. This surrender was brushed off the table by the KI on the basis of a motivation basedon themutual trust concerning thecompliance with fundamental rights within the context of European cooperation in criminal matters. This motivation seems bound to raise eyebrows amongst those who advocate this classic tenet of cross-border cooperation.This article frames this recent judgement within a European context, and investigates whether there is indeeda European tendency to step away from blind trust in lieu of (successfully) invoking fundamental rights to refuse cooperation. The case under scrutiny already seems to be pointing in that direction as far as the member states are concerned. Moreover, it seems to be confirmed by recent statements within the European Court of Justice (ECJ) by the Advocates General, as well as through the new procedural wind blowing through the Union with the Procedural Roadmap. On the other hand, the ECJ shows itself more reluctant than expected, giving rise to a situation in which member states and involved individuals remain in the dark with regard to a consistent line on the complex relation between smooth European cooperation in criminal cases and respect for fundamental rights. The Union moreover appears to be increasingly moving away from cooperation in criminal cases – despite the fact that it concerns a competence enshrined in treaty law – in exchange for a harmonisation of national (minimum) standards. A noble motive, which in this case however carries the potential to further complicate, or even undermine, the necessary trust and guarantees for fundamental rights in criminal cases. The recent judgement by the Court of Cassation also demonstrates that the matter of human rights requires an adequate response, not only to permanently ensure and improve the protection of fundamental rights, but also to avoid that more and more spanners are thrown in the works of smooth European cooperation in criminal matters